On the Knee joint arthroscopy – A Review with a Case study, - Kılıç, B., Yücel, A. S., Zekioğlu, A. (My University, 2014)
Arthroscopic surgical interventions can be performed as a surgical day case. The low morbidity of the arthroscopic surgery makes it attractive for both the surgeons and patients and it also has certain advantages such as small incision size and a small amount of bleeding and pain. Therefore, there is a possibility of early ambulation and discharge, which reduces risk of thrombophlebitis. The infection risk is also low due to the small incision size and the disinfection fluids used. Our study included 114 patients with a knee joint injury, on which arthroscopic partial meniscectomy was performed. We observed that pre-operation diagnoses made during physical and radiological examination matched 87% of those made during the surgery. It was also observed that 16 patients had fluid extravasation into the femoral and posterior tibial regions, 22 patients had post-op hemarthrosis, 15 patients had serous fluid blister, 11 patients suffered pain and ecchymosis for a period of 1 month on the side where the tourniquet was released, 9 patients experienced tibial collateral ligament injury and 18 patients had portal infection treated with antibiotics. 89% of problems the patients experienced disappeared.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Arthroscopy; arthroscopic partial meniscectomy; meniscectomy